Long-term engagement in smoking cessation campaign: A mixed methods randomized trial. - Robert Schwartz; Tracey Borland; Maaz Shahid; Karen Kuzmich; Michael Chaiton (PLoS ONE)
Introduction A long-term engagement (LTE) intervention was embedded in a social marketing campaign aimed at motivating quit attempts among Canadian adult commercial tobacco users 35 to 64 years of age. The purpose of this study was to examine the effectiveness and appeal of LTE within a marketing campaign. Methods 3,199 Canadians who smoked cigarettes aged 35-64 recruited using Facebook and Instagram advertisements were randomized into Intervention and Control groups. Over the course of two years, Intervention Group participants received monthly emails connecting them to campaign news and activities, Mini Surveys to inform campaign refinement, feedback opportunities via focus groups and interviews, financial incentives, and proactive knowledge exchange presenting study findings. Both groups responded to a baseline and follow-up surveys every six months. Results LTE Intervention Group participants engaged frequently with emails (unique opens, open rates, click rates, and total clicks). Compared with Control Group members, they had significantly higher rates of: unaided and aided campaign awareness; engagement with the social marketing campaign (website visits, social media visits, likes/shares); actions towards making quit attempts; quit attempts. Many participants expressed feelings of motivation, support, and a sense of belonging. Conclusions When embedded in a social marketing campaign, meaningful long-term engagement of adults who smoke cigarettes shows promise as an intervention to promote quitting behaviors. Implications Active long-term engagement can significantly amplify the effects of social marketing campaigns aimed at promoting quit smoking behaviours among adults. The active engagement approach applied indicates that frequent long-term engagement is more effective when done in a more holistic, empathetic manner. The intervention also allows for real-time learning to support campaign development. Trial registration ISRCTN94797633.